FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN IBU DALAM MENGHADAPI MENOPAUSE - Selpina Oktaviani; Ketut Resmaniasih (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2018)
ABSTRACT Background: Women tend to be anxious as through post-reproductive period is menopause, which they need special attention in health problems as well as improved quality of life. The high life expectancy at the age of non-productive also requires special attention in view of the number of inhabitants in the region of Indonesia is still quite high. Objective: This study aimed to analyze the factors that affect the level of maternal anxiety in the face of the menopause in Pahandut region. Methods: Using amethod cross sectional in which the measurement of the independent variables and the dependent, do all in the sametime.The total sample is 125 people taken bytechnique Proportional Random Sampling with the inclusion and exclusion criteria. Technique intake of data by media assisted interview questionnaire. The level of anxiety is measured by T-MAS(TaylorManifest AnxietyScale). Usingtest Chi Square 95% confidence level. Results: There is no a relationship between education and the level of anxiety because of the P-Value<a (0,386>0.05) with OR = 2.426, there is no relationship between the level of anxiety due to work with the P-Value>a (0.435>0.05 ) with OR = 2.285, there is a relationship between income levels of anxiety due to P-value<a (0.000<0.05) with OR =72.45, there is a relationship between husband support the anxiety level for P-value<a (0.016 <0.05) with OR =5.143 and OR =8.222. Suggestion: Can be followed a similar study that includes more analysis of the factors that may affect maternal anxiety facing menopause. Keywords: Dealing with menopause, menopausal anxiety, factors associated with menopause Abstrak Latar belakang: Perempuan cenderung cemas karena melalui post-reproductive masa menopause, yang mereka butuhkan khusus perhatian dalam masalah kesehatan serta peningkatan kualitas hidup. Harapan tinggi hidup pada usia non-produktif juga memerlukan perhatian khusus dalam jumlah penduduk di wilayah Indonesia masih cukup tinggi. Tujuan: Studi ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi tingkat kecemasan dalam menghadapi menopause di wilayah Pahandut. Metode: Menggunakan amethod cross sectional di mana pengukuran variabel independen dan dependent, dilakukan secara bersamaan. Jumlah sampel adalah 125 orang yang diambil dengan proporsional Random Sampling dengan kriteria inklusi dan eksklusi. Teknik pengambilan data oleh media dibantu wawancara kuesioner. Tingkat kecemasan diukur oleh T-MAS (TaylorManifest AnxietyScale). Dengan analisa data Chi – Square level kepercayaan 95 %. Hasil: Tidak ada hubungan antara pendidikan dan tingkat kecemasan karena P-value<a (0,386=